Potential association of specific Candida parapsilosis genotypes, bloodstream infections and colonization of health workers' hands. (25th July 2014) - Delfino, D.; Scordino, F.; Pernice, I.; Lo Passo, C.; Galbo, R.; David, A.; Barberi, I.; Criseo, G.; Cascio, A.; Romeo, O.; Roilides, E.
Abstract Fungal nosocomial infections continue to be a serious problem among hospitalized patients, decreasing quality of life and adding millions of euros to healthcare costs. The aim of this study was to describe the pattern of fungi associated with the hands of healthcare workers and to genotype Candida parapsilosis isolates in order to understand whether their high clinical prevalence stems from endemic nosocomial genotypes or from the real emergence of epidemiologically‐unrelated strains. Approximately 39% (50/129) of healthcare workers were positive for yeasts and among 77 different fungal isolates recovered, C. parapsilosis was the most frequent (44/77; 57%). Twenty‐seven diverse genotypes were obtained by microsatellite analysis of 42 selected blood and hand isolates. Most of the isolates from hands showed a new, unrelated, genotype, whereas a particular group of closely related genotypes prevailed in blood samples. Some of the latter genotypes were also found on the hands of healthcare workers, indicating a persistence of these clones within our hospital. C. parapsilosis genotypes from the hands were much more heterogeneous than clinical ones, thus reflecting a high genetic diversity among isolates, which is notably unusual and unexpected for this species.